Determination of total electron content (TEC) with the use of selected pseudo-random noise code / Amirah Aiyub - Aiyub, Amirah (2013)
Total Electron content (TEC) measurements are made mostly using GPS data because of the good global coverage of the GPS observation network. TEC is an integral of electron density as the signals propagate from the satellites to the Global Positioning System (GPS) receivers and identified as the parameter of the ionosphere that affects most of radio signals. The transmitted GPS signals must propagate through the ionosphere layer at the atmosphere before reaching the surface. The ionosphere layer can cause the effect of the GPS due to the electron density at this layer. It is the main source of error in the GPS positioning. The problem is considered as the ionospheric delay at the ionosphere layer. Ionization process is mainly caused by solar radiation whereas the density of electrons is very much dependant on location (latitude, longitude and height), time of the day, season as well as sunspot cycle. By using data in RINEX format, this project focuses on determination of the total electron content at selected GPS receiver stations since GPS satellites are regularly identified by their pseudorandom-noise (PRN) code number which also acknowledged as the unique identifier for GPS satellites. Besides that, time of the day and analysis using matlab leveling process were considered for calculating mean TEC.